Sistema de informação laboratorial para o COVID-19 - Rocha, Bruno Daniel Alves (2022)
COVID-19, a respiratory disease caused by SARS-CoV-2, first appeared in Wuhan, China, on 31 December 2019. It has since spread worldwide and developed into an ongoing pandemic. Currently, COVID-19 does not have a cure, and prevention is the only way to fight against it. During waves of higher infection cases, tracking the infected population becomes a difficult but crucial task. Only a COVID-19 test can diagnose a person, and RT-PCR tests are the most effective. PORTIC, the research centre for P.Porto, started using its laboratory for RT-PCR tests to diagnose COVID-19 for the P.Porto community and some health centres that belong to ARSN. During this process, the laboratory needs to manage all of the sample and testing information and report the test results. This information management became a burden, and the staff would lose most of the time with administrative tasks. This dissertation’s main objective is to develop a laboratory information system for PORTIC. This system must satisfy the elicited and specified requirements. For that purpose, multiple architectures were analysed, concluding that the clean architecture is the best option for this system. The system supports data importation from multiple external sources, report generation and exportation and the entire sample flow. Its development followed a scrum methodology where each requirement was validated through user acceptance tests at the end of each iteration. To evaluate the system’s success, the laboratory answered a questionnaire to determine the perceived usefulness and ease of use. This concluded that the system was successful since the questionnaire determined that it was extremely useful and easy to use. The developed system is an innovation on COVID-19 testing since there are no real options in the market, and different laboratories can reuse the system to tackle COVID-19 testing.